2007
DOI: 10.1207/s15324818ame2001_4
|View full text |Cite
|
Sign up to set email alerts
|

Standards-to-Standards Linkage Under Title III: Exploring Common Language Demands in ELD and Science Standards

Abstract: Under Title III of the No Child Left Behind (NCLB) Act of 2001 (NCLB, 2001b) every state needs to show linkage between state content standards and state English language development standards as input to the development of state English proficiency tests. This article argues that Title III presents a unique opportunity to explore how different content standards can be linked on a common dimension. This article focuses on evaluating the degree to which content standards, such as English language arts and scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Stevens et al (2000) (Bailey, 2007;Bailey & Butler, 2004). The alignment between the language demands implicit in ELP standards and those in content standards also raises a concern about the meaning of language proficiency in academic settings, that is, whether, on the face of it, achieving language proficiency standards prepares students for the language needed to achieve content standards (Bailey, Butler & Sato, 2005). The following subsection reviews different approaches to define academic English language and its characteristics.…”
Section: Limitations Of Existing Measures Of Ell Students' Elpmentioning
confidence: 99%
“…Stevens et al (2000) (Bailey, 2007;Bailey & Butler, 2004). The alignment between the language demands implicit in ELP standards and those in content standards also raises a concern about the meaning of language proficiency in academic settings, that is, whether, on the face of it, achieving language proficiency standards prepares students for the language needed to achieve content standards (Bailey, Butler & Sato, 2005). The following subsection reviews different approaches to define academic English language and its characteristics.…”
Section: Limitations Of Existing Measures Of Ell Students' Elpmentioning
confidence: 99%
“…Using the approach from Bailey et al (2007), external studies have confirmed that the TELL aligns closely with English Language Development Standards in Arizona (Stevens et al, 2015b), California (Stevens et al, 2015a), Texas (Frantz & Bailey, 2016), and the World-Class Instructional Design and Assessment (WIDA) Consortium (Stevens, 2015), which is composed of 41 U.S. states, territories, and federal agencies. All the alignment studies investigated specific aspects of linguistic forms and language functions and their proportional representations on both tests.…”
Section: Methodsmentioning
confidence: 97%
“…In the wake of state‐level content and English language proficiency assessments mandated by the No Child Left Behind federal educational law in the United States, psychometric research contributed to a lively debate in the field regarding how ELLs perform on state‐level standardized English‐medium tests in content areas such as mathematics, science, and other disciplines (Abedi & Gándara, ; Mahoney, ; Martiniello, ; Wolf & Leon, ), the impact of accommodations (Abedi & Hejri, ), and the linguistic demands and complexity of such assessments (Abedi, ; Bailey, Butler, & Sato, ; Bailey & Huang, ; Martiniello, ; Menken, ). Mislevy and Durán (, this issue) argue that we must move beyond traditional and proposed accommodation measures for large‐scale testing and toward a more dramatic re‐thinking of content‐area assessment (local and large‐scale, formative and summative) that recognizes assessments' “deep and systematic ties to authentic teaching and learning activities in sociocultural contexts.”…”
Section: Issues Of Assessmentmentioning
confidence: 99%